Study of serum adiponectin levels for early detection of type 2 diabetes mellitus and its complications on kidney - K. V., Harish; R., Hareesh; Savith, Akshatha (International Journal of Advances in Medicine, 2021)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder due to insulin resistance caused by destruction of beta cells of pancreas. Insulin resistance in newly diagnosed type 2 diabetes mellitus patients leads to hyperglycemia. Serum adiponectin is a more sensitive and specific biomarker for early detection of diabetic nephropathy than urinary microalbuminuria. Methods: This is a case-control study conducted in Akash Institute of Medical Sciences, A total 180 subjects (120 cases and 60 controls). All the subjects included after informed consent, blood samples and urine samples are collected from the all the subjects. The serum Adiponectin and was estimated by using enzyme-linked immunoassay (ELISA) and fasting blood sugar (FBS), post prandial blood sugar (PPBS) and renal function test (RFT) was also estimated by laboratory standard methods. Results: This study was evaluated the FBS, PPBS, RFT and serum adiponectin levels in patients with type 2 diabetes mellitus patients and compare them with healthy controls. The serum adiponectin levels more significantly elevated in newly diagnosed type 2 diabetes mellitus patients and compared with the healthy controls. The study also found that significantly elevated levels of FBS, PPBS and RFT in type 2 diabetes mellitus patients and compared with the healthy controls, The statistically significant levels of serum adiponectin in patients with type 2 diabetes mellitus and when compared with the controls (p= 0.0001). Conclusions: The study suggesting that the s estimation of serum adiponectin levels in newly diagnosed type 2 diabetes mellitus patients useful for early detection of diabetic nephropathy. Because elevated levels of serum adiponectin in patients with newly diagnosed type 2 diabetes mellitus, this levels are positively correlated with the FBS and PPBS.